FREQUENCY AND ANTIMICROBIAL RESISTANCE PATTERNS OF BACTERIA ISOLATED FROM ASPIRATION SPECIMENS OF PATIENTS WITH HIP AND KNEE INFECTIONS AT A HOSPITAL IN BAGHDAD - Ali Al-Zuhairi, Hadi Abdulah Abd; Hussein, Nadheema Hammood; Rasool, Khetam Habeeb (International Journal of Research -GRANTHAALAYAH, 2017)
The present study was carried out to determine the frequency of bacteria responsible for hip and knee infections at a hospital in Baghdad/Iraq and to get an updated knowledge about their antibiotic resistance pattern during a period of study which extended from 1 October, 2016 till 1 October, 2017. Identification of bacteria at species level was done by using Analytic Profile Index (API) system (Bio-Merieux, France). The antimicrobial susceptibility test was performed according to Kirby-Bauer (disk diffusion) technique. The frequency of positive aspiration of hip and knee joint infections cultures was 25(65.79%) cases out of 38 hip and knee joint aspiration. Out of 25 positive aspirations of hip and knee joint infections cultures, 3(12%) cultures gave mix growth of bacteria. Frequency of positive hip and knee joint infections cultures was higher in male than female patients, 19(76%) vs. 6(24%) (P-value ≤ 0.05). Out of 28 isolated bacteria, Gram positive was the most frequently isolated bacteria in hip and knee joint infection cultures, 22(78.6%) vs. 6(21.4%) (P-value < 0.05). Staphylococcus epidermidis was the most frequently isolated 13(46.5%) isolates followed by Staphylococcus aureus isolates 7(25%). On other hand Pseudomonas aeruginosa was the most frequently isolated Gram negative bacteria 3(10.7 %%) in hip and knee joint infection cultures. The most effective antibiotic on Gram-positive isolates was Vancomycin which showed 95.5%. In Gram negative bacteria the most effective antibiotics were Imipenem (100%) followed by Amikacin which showed sensitivity rate 83.33.